Heart rate reserve complements regional wall motion abnormality for predicting outcome in hypertensives during stress echocardiography. (3rd October 2022) - Peteiro Vazquez, J C; Ciampi, Q; Zagatina, A; Cortigiani, L; Arbucci, R; Saad, A K; Celeutkiene, J; Citro, R; Rodriguez-Zanella, H; Gaibazzi, N; Djordjevic-Dikic, A; Boshchenko, A; et al.
Abstract: Background: Stress echocardiography (SE) was recently upgraded to include imaging-independent heart rate reserve (HRR) which assesses cardiac sympathetic balance and is simply based on one-lead electrocardiogram present in the echo monitor. The value of HRR for risk stratification of hypertensive patients remains undetermined. Aim: To assess the prognostic value of SE with HRR in hypertensive patients in a prospective, large scale, multicenter, international, effectiveness study. Methods: From July 2016 to December 2020, we enrolled 2747 hypertensives (age 66±10 years, 1599 males, 58.2%; ejection fraction 61±8%) referred from 12 certified laboratories. All patients underwent clinically indicated SE. The employed stress modality was exercise (n=754) or pharmacological stress (n=1993). Exercise modality was either semi-supine bike (n=674) or treadmill (n=80). Pharmacological stress was either vasodilator (n=1695, 1661 with dipyridamole and 34 with adenosine) or dobutamine (n=298). SE response included the evaluation of regional wall motion abnormality (RWMA) and non-imaging HRR (peak/rest heart rate), with stress-specific cutoff values abnormal response <1.80 for exercise or dobutamine, <1.22 for dipyridamole or adenosine. All-cause death was the only end-point. Results: Rate of abnormal results was 17% for RWMA and 40% for HRR. During a median follow-up of 624 days (interquartile range: 380–1037 days), 60 deaths occurred. Global X 2 was 25.0 considering clinical and resting echocardiographic variables, with no change after stress-induced RWMA and a significant increase after HRR (Figure 1). Annual mortality rate was 0.7% person/year for patients (n=1496) with normal HRR and absence of stress-induced RMWA, 0.4% for patients (n=151) with RWMA and normal HRR, up to 2.1% person/year for patients (n=1101) with abnormal HRR with (n=321) or without (n=780) RWMA. At multivariable analysis, only age (HR: 1.070, 95% CI: 1.039–1.101, p<0.001) and abnormal HRR 2.651 (HR: 2.651, 95% CI: 1.550–4.543, p<0.001) showed independent value in predicting survival. Conclusion: SE with either exercise or pharmacological stress allows an effective prediction of survival in hypertensive patients with chronic coronary syndromes, but only when the conventional criterion of RWMA is complemented with imaging-independent HRR. Funding Acknowledgement: Type of funding sources: None.